Effectiveness of a non-physician community health-care provider-led intensive blood pressure intervention versus usual care on cardiovascular disease (CRHCP): an open-label, blinded-endpoint, cluster-randomised trial. Issue 10380 (18th March 2023) - He, Jiang; Ouyang, Nanxiang; Guo, Xiaofan; Sun, Guozhe; Li, Zhao; Mu, Jianjun; Wang, Dao Wen; Qiao, Lixia; Xing, Liying; Ren, Guocheng; Zhao, Chunxia; Yang, Ruihai; et al.
Summary: Background: Effectiveness of a non-physician community health-care provider-led intensive blood pressure intervention on cardiovascular disease has not been established. We aimed to test the effectiveness of such an intervention compared with usual care on risk of cardiovascular disease and all-cause death among individuals with hypertension. Methods: In this open-label, blinded-endpoint, cluster-randomised trial, we recruited individuals aged at least 40 years with an untreated systolic blood pressure of at least 140 mm Hg or a diastolic blood pressure of at least 90 mm Hg (≥130 mm Hg and ≥80 mm Hg for those at high risk for cardiovascular disease or if currently taking antihypertensive medication). We randomly assigned (1:1) 326 villages to a non-physician community health-care provider-led intervention or usual care, stratified by provinces, counties, and townships. In the intervention group, trained non-physician community health-care providers initiated and titrated antihypertensive medications according to a simple stepped-care protocol to achieve a systolic blood pressure goal of less than 130 mm Hg and diastolic blood pressure goal of less than 80 mm Hg with supervision from primary care physicians. They also delivered discounted or free antihypertensive medications and health coaching for patients. The primary effectiveness outcome was a composite outcome of myocardial infarction, stroke, heart failure requiring hospitalisation, and cardiovascular disease death during the 36-month follow-up in the study participants. Safety was assessed every 6 months. This trial is registered with ClinicalTrials.gov, NCT03527719 . Findings: Between May 8 and Nov 28, 2018, we enrolled 163 villages per group with 33 995 participants. Over 36 months, the net group difference in systolic blood pressure reduction was –23·1 mm Hg (95% CI –24·4 to –21·9; p<0·0001) and in diastolic blood pressure reduction, it was –9·9 mm Hg (–10·6 to –9·3; p<0·0001). Fewer patients in the intervention group than the usual care group had a primary outcome (1·62% vs 2·40% per year; hazard ratio [HR] 0·67, 95% CI 0·61–0·73; p<0·0001). Secondary outcomes were also reduced in the intervention group: myocardial infarction (HR 0·77, 95% CI 0·60–0·98; p=0·037), stroke (0·66, 0·60–0·73; p<0·0001), heart failure (0·58, 0·42–0·81; p=0·0016), cardiovascular disease death (0·70, 0·58–0·83; p<0·0001), and all-cause death (0·85, 0·76–0·95; p=0·0037). The risk reduction of the primary outcome was consistent across subgroups of age, sex, education, antihypertensive medication use, and baseline cardiovascular disease risk. Hypotension was higher in the intervention than in the usual care group (1·75% vs 0·89%; p<0·0001). Interpretation: The non-physician community health-care provider-led intensive blood pressure intervention is effective in reducing cardiovascular disease and death. Funding: The Ministry of Science and Technology of China and the Science and Technology Program of Liaoning Province, China.